Civic behavior of university professors in the educational context - Pérez Salazar, Sixto (2022)
The purpose of this work was to determine the citizen behaviors carried out by professors from two universities in the State of Morelos, Mexico. These behaviors are those carried out by the teachers in favor of the students, they were obtained through a qualitative exploratory study with the application of semi-structural interviews to the participants, each interview was transcribed coding the detected citizen behaviors, which were analyzed and selected by category and subcategories according to their nature, the interviews stopped until reaching the theoretical saturation of the construct, according to the methodology of the fundamental theory based on the data of Strauss & Corbin (2002). To carry out the interviews, the protocols indicated by the Research Ethics Committee of the Center of Transdisciplinary Research in Psychology (CEI-TIPsi) of the Autonomous University of the State of Morelos (UAEM) were followed. The sample was selected by the snowball method, which consisted of 19 professors, 11 belonging to a public university and 8 belonging to a private university. Four categories of citizen behavior of university professors towards students were determined: 1. Courtesy and harmonization: a) Teacher-student trust, b) Adequate study environment, and c) Introduction of the professor, the class and the course; 2. Facilitation of progress in tasks: a) Encouraging increased learning, and b) Facilitation of teaching activities; 3. Motivation and support: a) Motivation of the students for it learning, and b) Understanding and helping the student with problems; and 4. Efficiency in teaching: a) Improving the efficiency of the course. These behaviors are developed by university professors in their daily interaction with students when performing their main education and training functions, they are not assumed as part of the activities to be carried out, although some professors assume them as part of their psychological contract, others perform them of their own free will and as a moral duty to help because of the meaning of what it is being a teacher.